IMPACTUL POPULISMULUI ASUPRA ECHILIBRULUI DE PUTERE ÎN UNIUNEA EUROPEANĂ. AMENINȚARE HIBRIDĂ LA ADRESA INTEGRITĂȚII UNIUNII EUROPENE - Maria-Lorena REIT (Intelligence și Cultura de Securitate)
This article begins with a brief introduction to European populism, defining it and explaining its main characteristics, in order to provide a general context for the analysis. The paper is structured in four parts, while explaining how populism can be perceived as a hybrid threat to the European Union and analyzing the impact that this phenomenon has on the balance of power between the member states of the Union, , as well as on the global balance of power. In the first part of the paper, I analyzed the features of Hungarian and Polish populism, analyzing the discourses of PiS and Fidesz representatives. In this sense, I undertook a comparative analysis of the discursive structures of the two parties, highlighting the similarities and differences identified in the rhetoric of Viktor Orbán and Jarosław Kaczyński. In the second part of the article, I framed populism among hybrid threats, examining how this ideology can be perceived as such a threat. In the third part of the paper, I analyzed how populism affects the balance of power, approaching this theme from three perspectives, namely from the perspective of the balance of power between the member states, from the inter-institutional perspective, as well as from the perspective of the international balance of power. In the fourth part of the paper, I analyzed the actions that the European Union can take to reduce the effects generated by populism. In this sense, I brought up three means of counteracting this phenomenon, namely the use of the sanctions provided for in art. 7 of the Treaty on the European Union, the suspension from the Schengen area and the implementation of financial pressures, reaching the conclusion that financial sanctions would be the main way to force populist parties to give up this ideology. Following this research, the main conclusion I reached is that the hybrid threat character of populism and its impact on the balance of power are the collective result of populist parties in the Union. More precisely, although the two analyzed parties are the most representative for this phenomenon, the ability to influence the balance of power is possible due to the extent of the phenomenon in the European Union.